Estimated neonatal survival of very preterm births across the care pathway: a UK cohort 2016–2020 - Seaton, SE; Agarwal, R; Draper, ES; Fenton, AC; Kurinczuk, JJ; Manktelow, BN; Smith, LK (BMJ Publishing Group, 2023)
Objective Currently used estimates of survival are nearly 10 years old and relate to only those babies admitted for neonatal care. Due to ongoing improvements in neonatal care, here we update estimates of survival for singleton and multiple births at 22+0 to 31+6 weeks gestational age across the perinatal care pathway by gestational age and birth weight.